Masyarakat Warga dan Problem Keberadaban - Sudibyo, Agus (Jurnal Ilmu Sosial dan Ilmu Politik, 2010)
The emergence of civil society in Indonesia has always been located in a framework to deal with such a strong state hegemony. Civil society is located as the antithesis to the state. This article argues that civil society in Indonesia is also facing the threat of the existence of civil society itself, so uncivil society emerged as a threat to civil society that comes from civil society itself. In addition, a serious threat to civil society also emerged from the stronger market intervention.